2012
DOI: 10.1017/jns.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Cacao liquor procyanidin extract improves glucose tolerance by enhancing GLUT4 translocation and glucose uptake in skeletal muscle

Abstract: Hyperglycaemia and insulin resistance are associated with the increased risk of the metabolic syndrome and other severe health problems. The insulin-sensitive GLUT4 regulates glucose homoeostasis in skeletal muscle and adipose tissue. In this study, we investigated whether cacao liquor procyanidin (CLPr) extract, which contains epicatechin, catechin and other procyanidins, improves glucose tolerance by promoting GLUT4 translocation and enhances glucose uptake in muscle cells. Our results demonstrated that CLPr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 57 publications
5
50
0
Order By: Relevance
“…The differentiation of L6 myoblasts to myotubes (4.0 × 10 3 cells) was performed according to the previously described method. 26) The cells were maintained in MEM containing 10% FBS for two days and incubated with MEM containing 2% FBS. Differentiated L6 myotubes were serum starved in MEM containing 0.2% BSA for 18 h. Serum-starved L6 myotubes were treated with 0.1, 1, and 3 µM EGC-M5 for 15 min and subjected to Western blotting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation of L6 myoblasts to myotubes (4.0 × 10 3 cells) was performed according to the previously described method. 26) The cells were maintained in MEM containing 10% FBS for two days and incubated with MEM containing 2% FBS. Differentiated L6 myotubes were serum starved in MEM containing 0.2% BSA for 18 h. Serum-starved L6 myotubes were treated with 0.1, 1, and 3 µM EGC-M5 for 15 min and subjected to Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose uptake was determined by enzymatic fluorescence assay for 2-DG uptake in myotubes. 26) This evaluation was according to the procedure used for other dietary polyphenols. [27][28][29] Serumstarved L6 myotubes in a 96-well plate were treated with 11 kinds of metabolites dissolved with dimethyl sulfoxide (DMSO) at a final concentration of 3 µM for 4 h in 0.2% (w/v) BSA/MEM.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed skeletal muscle plays a crucial role in maintaining glucose homeostasis as it accounts for almost 80% of insulin‐stimulated glucose uptake in the postprandial state . Cacao liquor procyanidin extract (CLPr), which is rich in catechins and B‐type proanthocyanidins oligomers, increased glucose uptake in a dose‐dependent manner in L6 myotubes (maximum effect at 5 μg/mL) by inducing GLUT‐4 translocation, whereas GLUT‐1 and ‐4 levels did not change in the plasma membrane .…”
Section: Antidiabetic Actions Of Cocoa Flavonoidsmentioning
confidence: 99%
“…It is well known that glucose uptake requires translocation of GLUT4 transporter from intracellular space to the plasma membrane. This process can be enhanced by AMPK-signaling pathways by procyanidins (Yamashita et al, 2012). Our results indicated that JQ polyphenolic compounds can increase GLUT4 gene expression to some extent.…”
Section: Figure 2 the Effect Of Jq (5 Mg/ml) And Metformin (2 Mm) 24mentioning
confidence: 61%